We Must Believe that Everything is Meaningfully Ordered (KULT_online, 2006)
Ernst Jünger. Politik - Mythos - Kunst is an anthology of essays originally presented at a symposium of the same name in 2002. The essays explore the work of Ernst Jünger from a variety of perspectives and utilize a multiplicity of methodological approaches, with the sub-title providing a focus for the anthology as a whole. The general picture of Jünger that emerges is of an important author, one whose proximity to the central experiences of the German nation in the 20th century and the political, mythic and artistic strategies he employed informed his unique, provocative and controversial literary voice.